Expression Pattern of Cathelicidins in Dairy Cows During Endometritis and Role of Bovine Endometrial Epithelial Cells in Production of Cathelicidins - Li, Yajuan; Ma, Xiaoyu; Yang, Jie; Wu, Xiaohu; Yan, Zuoting; He, Baoxiang (Frontiers in Veterinary Science, 2021)
Endometritis is a common bacterial disease of dairy cows. Cathelicidins are host-defence peptides that play important roles in clearance of bacteria. The precise role of these peptides during endometritis is still unclear. This study was to investigate the changes of bovine cathelicidins during endometritis. Forty-four postpartum cows (28~35 days after calving) involved in this study were grouped according to the character of vaginal discharge (VD) into three groups. These were 1) cows with clear fluid (n=8, normal cows group, N); 2) cows with VD containing < 50% off-white mucopurulent material (n=20, moderate endometritis cows group, M); 3) cows with VD containing > 50% yellow or white purulent material (n=16, severe endometritis cows group, S). The blood, VD, and endometrial biopsies samples were collected from each cow to assess the levels of cathelicidin1~7. Furthermore, bovine endometrial epithelial cells (BEECs) were stimulated with different concentration of E. coli (2×106 and 2×107 CFU/mL) to detect the cellular source of cathelicidins. Quantitative real-time PCR (RT-qPCR) was used to detect the relative mRNA expression of cathelicidins, and enzyme-linked immune sorbent assay (ELISA) method were used to measure the protein levels. The mRNA and protein levels of cathelicidin 1~ 7 significantly increased during bovine endometritis (both moderate and severe endometritis), while samples from severe cases showed lower levels of cathelicidins compared to moderate cases. BEECs can express cathelicidin 1~7, and E. coli triggered the release of these proteins. High concentration of E. coli decreased the mRNA and protein levels of cathelicidins. Taken together, our results supported that cathelicidins are released as host defence molecules against the bacteria during bovine endometritis, and BEECs play an active role in expression and production of cathelicidins.